Geomorphological Assessment of the Viability of the Landforms in the Khalekan Valley Basin for Human Uses (Raparin Journal of Humanities (RJH), 2021)
The study aims to evaluating the landform in the khalakan basin and its to preparing appropriate model for the capacity of the lands by using remote sensing (RS) technology and geographic information system (GIS) by depending on function of (Wighted-Overlay) which can be considered as one of the significant function of GIS. And in order to achieve the aim of the study, eight layers have been extracted for preparing appropriate ground model. according to the importance of each layer which is used to determine the ability and they are: (geological formations, slope, splash erosion, soil, plant cover (NDVI), elevation and lineaments, geomorphological unit) layers which can be considered as the result of Intrusive and extrusive processes. After the processes of Overlaying, the study successfully produced a general map for the appropriateness ground which categorized the area into three levels of appropriateness: the level of high appropriateness with area of(9.34Km), the level of mid appropriateness with area of (70.34Km) and the level with no appropriateness with area of (4.957Km.